National Policy for Integrated Development in the Himalayas Report of the Expert Group - Planning Commission (Planning Commission Government of India, 1993)
The Integrated Development in the Himalayas Report presents a comprehensive framework for sustainable socio-economic development in the Himalayan region, balancing human needs with ecological preservation. The report identifies key challenges, including fragmented landholdings, inadequate infrastructure, ecological vulnerability, poverty, unemployment, and gender disparities in agricultural participation. It advocates holistic strategies encompassing sustainable agriculture, watershed management, eco-tourism, forest conservation, alternative energy adoption, and local infrastructure development. Emphasizing community involvement, particularly women’s empowerment, the report recommends the establishment of a Himalayan Development Authority and a dedicated Environment & Development Fund to coordinate integrated initiatives. By combining environmental protection with economic growth, the strategy aims to enhance livelihoods, resilience, and long-term sustainability of Himalayan communities.
Planning Commission Government of India New Delhi
Keywords: Himalayan Development; Sustainable Agriculture; Ecological Conservation; Community Participation; Women Empowerment; Watershed Management; Eco-Tourism; Rural Infrastructure; Forest Preservation; Integrated Planning; Alternative Energy; Socio-Economic Upliftment